Combined effect of pulse electron beam treatment and thin hydroxyapatite film on mechanical features of biodegradable AZ31 magnesium alloy; IOP Conference Series: Materials Science and Engineering; Vol. 98 : Interdisciplinary Problems of Nanotechnology, Biomedicine and Nanotoxicology (Nanobiotech 2015) - Surmeneva M. A. Maria Alexandrovna; Tyurin A.; Teresov A.; Koval A.; Pirozhkova T.; Shuvarin I.; Surmenev R. A. Roman Anatolievich (2015, 2015)
Title screen